Development, calibration and validation of weighing lysimeters for measurement of evapotranspiration of crops - Fenner,William (2019)
ABSTRACT The evapotranspiration process is critical to studies on the water balance and water demand of crops and can be determined by several methods. A widely-used method, despite its high installation costs, is weighing lysimeters, which consists of a box over a balance connected to a load cell that monitors variations in the soil-water-plant-atmosphere system. The aim of this study was to develop and calibrate six weighing lysimeters (with dimensions of 1.5 x 1.5 x 1.2 m each) by high precision load cells, testing their ability to measure water mass changes in field conditions and cultivated with common bean (Phaseolus vulgaris L.), in the city of Tangará da Serra, in the state of Mato Grosso, Brazil. All lysimeters showed coefficients of determination higher than 0.99, as well as Willmott indexes, correlation and high confidence indexes, indicating that the equipment is suitable for measuring mass variations in water balance and evapotranspiration studies, representing the reality which occurred in the field.